An Analysis of Studentsâ Skill in Using Degree of Comparison at Second grade Sudents of SMAN 1 Bangun Purba - Adifatri, Yose; Rasyidah, Ummi; -, Eripuddin (Jurnal Ilmiah Mahasiswa FKIP Prodi Bahasa Inggris, 2015)
The purpose of this research was toknow the skill of the second grade students ofSMAN 1 Bangun Purba of studentsâ skill in usingdegree of comparison. The participant of thisresearch weresecond grade students of SMAN 1Bnagun Purba Kabupaten Rokan Hulu. consists of25 students. The kind of sample is âtotal samplingâand it had been taken all of the population. Theresearch was descriptive qualitative research. Theresult of this research showed that the skill ofsecond grade students of SMAN 1 Bangun Purbawas 59,4 or in fair category. While for studentsskill in using postive degree of comparison was74,4 or in good category, while students skill inusing comparative degree was 56,36 or in faircategory, and students skill in using superlativedegree was 48,58 or in fair category.